Synthesis and anticancer properties of 1-(2-isopropyl-5-methylphenoxymethyl)-3R-4-aryl-5,6,7,8-tetrahydro-2,2а,8а-triazacyclopenta[cd]azulene derivatives - S. A. Demchenko; A. E. Dudnik; T. A. Bukhtiarova; L. S. Bobkova; A. M. Demchenko (The State Expert Center of the Ministry of Health of Ukraine, 2018)
In recent years, attention to itself is attracted to the problem of treatment of cancer that is caused by increase in patients, especially of working age. Therefore, the enlargement of the arsenal of anticancer medicines of a wide spectrum of action is actual. The purpose of the study was to synthesize substances with potentially antitumor properties in a series 1-(2-isopropyl-5-methylphenoxymethyl)-3R-4-aryl-5,6,7,8-tetrahydro-2,2а,8а-triazacyclopenta[cd]azulene derivatives and to study the effect of synthesized compounds on inhibition of growth (or their destruction) of a wide range of cancer. The objects of the study were derivatives of 1-(2-isopropyl-5-methylphenoxymethyl)-3R-4-aryl-5,6,7,8-tetrahydro-2,2а,8а-triazacyclopenta[cd]azulene, which were synthesized by refluxing 3-(2-isopropyl-5-methylphenoxymethyl)-6,7,8,9-tetrahydro-5Н-[1,2,4]triazolo[4,3-a]azepine with с appropriate α-halogenketones in ethyl acetate and further cyclization in an alkaline medium. Использовали данные NMR 1Н spectroscopy data were used. The primary evaluation of anticancer activity was carried out National Cancer Institute of Health, USA within the Development Therapeutic Program. A series of new of 1-(2-isopropyl-5-methylphenoxymethyl)-3R-4-aryl-5,6,7,8-tetrahydro-2,2а,8а-triazacyclopenta[cd]azulene derivatives was synthesized, their structure and purity were confirmed by NMR 1Н spectroscopy. The anticancer activity of the synthesized compounds was studied both at a concentration of 10-5 mol/l and in a concentration gradient of 10-4‒10-8 mol/l in experiments in vivo on cancer cell lines. It is shown that insertion of methyl group into position 3 of heterocyclic system of the basic structure of 4-aryl-5,6,7,8-tetrahydro-2,2a,8a-triazacyclopenta[cd]azulene leads to an increase in the anticancer effect. It is found that the tested compounds showed high anticancer effect on all types of cancer cell lines investigated - leukemia, non-small cell lung cancer, colon cancer, CNS cancer, melanoma, ovarian cancer, renal cancer, prostate cancer and breast cancer.